2017
DOI: 10.3945/cdn.117.000638
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Vitamin K Forms Exist in Dairy Foods

Abstract: Background: The plant-based form of vitamin K (phylloquinone, vitamin K-1) has been well quantified in the US diet. Menaquinones (vitamin K-2) are another class of vitamin K compounds that differ from phylloquinone in the length and saturation of their side chain, but they have not been well characterized in foods. Objectives: The objectives of this study were to 1) quantify phylloquinone and the different forms of menaquinones [menaquinone (MK) 4–MK13] in milk, yogurt, Greek yogurt, creams, and cheeses and 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 30 publications
0
58
2
Order By: Relevance
“…Remarkably, the menaquinone content of typical Dutch hard cheeses (Gouda, Edam) was relatively high compared to most soft cheeses as produced in Mediterranean countries. This is in contrast to a recent study from the USA [ 22 ], in which soft cheeses were found to contain on average about twice as much menaquinones as hard cheeses. This demonstrates the necessity of having national databases for menaquinone content of food.…”
Section: Discussioncontrasting
confidence: 99%
“…Remarkably, the menaquinone content of typical Dutch hard cheeses (Gouda, Edam) was relatively high compared to most soft cheeses as produced in Mediterranean countries. This is in contrast to a recent study from the USA [ 22 ], in which soft cheeses were found to contain on average about twice as much menaquinones as hard cheeses. This demonstrates the necessity of having national databases for menaquinone content of food.…”
Section: Discussioncontrasting
confidence: 99%
“…Vitamin K 2 includes a range of vitamin K isoforms that differ structurally from vitamin K 1 also known as phylloquinones, which are mainly found in leafy green vegetables. Vitamin K 2 is the most biologically active form of vitamin K and it has a longer half-life than vitamin K 1 [ 36 , 218 , 219 ]. A growing body of evidence suggests that vitamin K has beneficial effects on cardiovascular health [ 220 , 221 , 222 , 223 ].…”
Section: Fermented Dairy Products and Cardiovascular Healthmentioning
confidence: 99%
“…In comparison to other foods, fermented dairy and other animal products have a high content of vitamin K 2 . Fermented dairy products, in particular cheese, yoghurt and kefir contain vitamin K 2 [ 219 , 225 ], thus consumption of fermented dairy products may be beneficial for human cardiovascular health. Randomised trials have provided some evidence to support the beneficial effects of vitamin K 2 on bone health and some intervention trials that assessed vitamin K in conjunction with vitamin D have demonstrated positive results on cardiovascular-related outcomes [ 36 ].…”
Section: Fermented Dairy Products and Cardiovascular Healthmentioning
confidence: 99%
“…100 g, and that reduced-fat products contained 5%-22% of the vitamin K found in full-fat equivalents. 30 K2 in cheese originates from bacterial processes present at the start of the cheese-making process. 26 As different lactic acid bacteria are used in cheese making, a large variability in K2 content is found.…”
Section: Open Accessmentioning
confidence: 99%
“…25 However, these recommendations may not be sufficient to attain complete carboxylation of extrahepatic vitamin K-dependent proteins. 26 27 Given the limited number of epidemiological studies, [18][19][20][21][22][23][24] and the fact that dietary vitamin K sources and content differ between countries, [28][29][30][31] further research is warranted. The purpose of the current study was to evaluate the association between intake of both K1 and K2 and subsequent CHD events among community-living middle-age adults in Norway.…”
Section: Introductionmentioning
confidence: 99%